A Drug‐Self‐Gated Mesoporous Antitumor Nanoplatform Based on pH‐Sensitive Dynamic Covalent Bond. (3rd February 2017) - Zeng, Xiaowei; Liu, Gan; Tao, Wei; Ma, Yue; Zhang, Xudong; He, Fan; Pan, Jianming; Mei, Lin; Pan, Guoqing
Abstract : To achieve on‐demand drug release, mesoporous silica nanocarriers as antitumor platforms generally need to be gated with stimuli‐responsive capping agents. Herein, a "smart" mesoporous nanocarrier that is gated by the drug itself through a pH‐sensitive dynamic benzoic–imine covalent bond is demonstrated. The new system, which tactfully bypasses the use of auxiliary capping agents, could also exhibit desirable drug release at tumor tissues/cells and enhanced tumor inhibition. Moreover, a facile dynamic PEGylation via benzoic–imine bond further endows the drug‐self‐gated nanocarrier with tumor extracellular pH‐triggered cell uptake and improves therapeutic efficiency in vivo. In short, the paradigm shift in capping agents here will simplify mesoporous nanomaterials as intelligent drug carriers for cancer therapy. Moreover, the self‐gated strategy in this work also shows general potential for self‐controlled delivery of natural biomolecules, for example, DNA/RNA, peptides, and proteins, due to their intrinsic amino groups. Abstract : A drug‐self‐gated strategy for mesoporous nanocarrier could achieve on‐demand drug release at tumor tissue/cells and improved antitumor efficiency. The key is using a pH‐sensitive benzoic–imine bond for dynamic conjugation of amino‐containing drug molecules (i.e., doxorubicin) on the pore outlets.